BANK PERKREDITAN RAKYAT: TEROBOSAN STRATEGIS BAGI PENGUATAN KELEMBAGAAN DAN PEMBIAYAAN USAHA KECIL - M. Syahirman Yusi (Jurnal Keuangan dan Perbankan, 2014)
Capital shortage was the main problem faced by the small scale enterprises. To solve the problem, in 2013 thegovernment legislated the regulations no. 1 about microfinance. Rural banking or BPR was one of microfinanceprograms offered the capital and other policies to improve the small scale enterprises. This paper aimed toreview the development strategy of the rural banking that supported small scale of food enterprise effectivelyin the form of financing, strengthening, and partnership in South Sumatera. Survey and interview techniquewere implemented to 225 samples and the data was analyzed by using both one way Anova Test and StructuralEquation Modeling. The result of analysis showed that all of the program offered by the rural banking hadsupported the development of small scale enterprises. Further analysis indicated that not only proposedresearch hypothesis but also the theoretical model were not rejected.